Inequality in Europe: What can be done? What should be done? - Maurizio Franzini; Michele Raitano; Tim Callan; Brian Nolan; Claire Keane; Michael Savage; John R. Walsh; Gerhard Bosch; Stéphane Bonhomme; Laura Hospido; Ive Marx (Intereconomics, 2013)
As economic inequality in Europe has continued to rise, it has become the subject of increasing academic attention. What are the drivers of inequality? How does it affect intergenerational economic and social mobility? At what point does inequality become a drag on economic growth or a threat to social order? What economic policy tools are available to reduce inequality? This Forum addresses these and other aspects of this complex and disturbing trend. Case studies of Ireland, Germany and Spain also highlight the impact of economic inequality on individual member states.
Keywords: 330